Acute myocarditis in a patient with parainfluenza infection, seven years after bone marrow transplantation - Nikolay Marinov; Iana Simova; Ivo Petrov (Българска кардиология, 2020)
Myocarditis is an inflammatory disease of the myocardium, with heterogeneous etiology.  Although rare, myocarditis can be a complication of the influenza infection. In the majority of cases, viral myocarditis is a self-limiting infection passing without permanent changes in the myocardium. We present a clinical case of a 30-year-old woman with acute heart failure in the course of respiratory infection accompanied by severe systolic dysfunction (left ventricular (LV) ejection fraction (EF) 16%). The patient was treated according to the current guideline recommendations for the treatment of acute and chronic heart failure with the conjunction of immunomodulating and metabolic therapy. During hospitalization from microbial and viral testing, acute-phase antibodies to parainfluenza virus were identified. Following the treatment, a complete resolution of heart failure symptoms and restoration of LVEF to baseline (40%) was observed. Timely initiation of treatment in myocarditis, followed by good clinical course and regression of LV systolic dysfunction, in some cases may cancel invasive procedures such as endomyocardial biopsy.